CATCH ANALYSIS IN 1974 AND FBHING TRENDS IN THE JAISAMAND LAKE (RAJASTHAN) - Durve, V S; Kakkar, Virendra (Indian Journal of Fisheries, 2011)
The lake Jaisamand, one of the most productive lakes in India, is situatedsoutheast of Udaipur. The lake has been in existence for more than the last 250years. In spite of indiscriminate exploitation, without observing closed seasontill 1970 atid any restriction on the mesh-size, and without stocking, this supporteda sizable fishery since 1949